The Law of Gender Justice in Digital Inheritance Distribution: A Fiqh Perspective on Crypto Assets and Non-Fungible Tokens in Dubai - Khotimah, Umi Khusnul (SASI, 2025)
Introduction: The rapid development of digital technology has introduced new challenges in the practice of inheritance distribution, particularly concerning digital assets such as cryptocurrency and NFTs.Purposes of the Research: This study aims to explore gender justice in the distribution of digital inheritance, focusing on the Islamic fiqh perspective toward cryptocurrency and NFTs assets in Dubai.Methods of the Research: Using a qualitative approach, the research analyzes fiqh texts, existing regulations, and real-life cases related to digital inheritance. Data were collected through document analysis, case studies, and expert interviews involving Islamic scholars and digital asset practitioners in Dubai.Results of the Research: The findings reveal that digital inheritance, characterized by unique properties such as anonymity and the need for secure access, presents significant challenges in ensuring fair distribution, especially for women. The study highlights cultural and technological barriers that limit women’s access to digital inheritance, despite their growing economic contributions. The novelty of this research lies in proposing a contemporary fiqh framework that integrates traditional Islamic principles with modern technological solutions such as blockchain, aiming to ensure transparency and fairness in inheritance distribution. By addressing the gender gap in digital inheritance, this research contributes to the development of equitable and practical fiqh guidelines for Muslim communities in the digital era.